PENGARUH SENTIMEN PASAR TERHADAP PERGERAKAN HARGA SAHAM PADA PERUSAHAAN INDUSTRI MANUFAKTUR PADA BURSA EFEK INDONESIA - Utami, Hermin Ayu; Herwiyanti, Eliada; Suparlinah, Irianing (Jurnal Ekonomi, Bisnis, dan Akuntansi; Vol 26 No 1 (2024): Regular Issue, 2024)
The purpose of this research is to find out the changes in the stock price based on the news that affect the sentiment of the market in Indonesia. The research was carried out on the manufacturing company and its sub-sector on the companies listed on the Indonesian Stock Exchange. The study used a descriptive method with a quantitative approach, and used secondary data such as the highest stock price data, lowest, closure, price differential, trading volume, stock value, purchase frequency obtained from the website www.idx.co.id. Data taken only 2 months at the time of the boycott of pro-Israeli products in Indonesia. The study was to find the change in the price of the stock based on news that affected the sentiment in the market. The investigation was conducted on manufacturing companies and the sub-sectors on which the company is listed in the Indonesia Stock Exchange. The research used a describing method with the qualitative approach and, using secondary information such as highest price of shares, the lowest price, the decline, the value of the product on the website of the manufacturer, the volume of which is taken from the month of the purchase of the products.